2022
DOI: 10.1039/d2ta01798a
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly magnetized 3D hierarchical graphite carbon-based heterogeneous yolk–shell nanoboxes with enhanced microwave absorption

Abstract: Graphite carbon is transformed from thin layers into a 3D hierarchical structure via self-assembly during a specific hydrothermal process. Nano-scale magnetic coupling networks and various forms of losses play active roles in microwave absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…In general, the real part of complex permittivity (3 ′ ) and complex permeability (m ′ ) reects the ability of absorbers to store electromagnetic energy, while the imaginary part of complex permittivity (3 ′′ ) and complex permeability (m ′′ ) represents the loss capability of energy. 46 As shown in Fig. 5a and b, due to the introduction of MXene networks, both the 3 ′ and 3 ′′′ of ZFCM series are signicantly elevated.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In general, the real part of complex permittivity (3 ′ ) and complex permeability (m ′ ) reects the ability of absorbers to store electromagnetic energy, while the imaginary part of complex permittivity (3 ′′ ) and complex permeability (m ′′ ) represents the loss capability of energy. 46 As shown in Fig. 5a and b, due to the introduction of MXene networks, both the 3 ′ and 3 ′′′ of ZFCM series are signicantly elevated.…”
Section: Resultsmentioning
confidence: 94%
“…5g and S19 †), which may arise from interfacial polarization and dipolar polarization. 23,46 The continuous interfaces between the three phases of MXene, carbon matrixes, and magnetic nanocrystals can signicantly trigger the interfacial polarization. 50 The residual end groups, the intrinsic defects, and the oxidation-generated defects of MXene as well as the defects in carbon matrixes can lead to the asymmetry of electron spatial distribution and the formation of dipole moment, resulting in dipolar polarization under microwave irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in the range of 1200–1800 cm –1 , HMCS and all HMCS@f-Fe 2 O 3 - x samples demonstrated two distinguishable peaks, that is, one broad peak centered at ∼1340 cm –1 (D-band) and the other relatively sharp peak at ∼1590 cm –1 (G-band) in Figure c. It has been well documented that the intensity ratio of D-band to G-band ( I D / I G ) is usually utilized to estimate the graphitization degree. , However, it could be found that all samples displayed similar I D / I G values, indicating that the carbon components in these composites have a similar graphitization degree. Moreover, TG curves were carried out to determine the weight fractions of f-Fe 2 O 3 in HMCS@f-Fe 2 O 3 - x composites (Figure d).…”
Section: Resultsmentioning
confidence: 96%
“…It has been well documented that the intensity ratio of D-band to G-band (I D /I G ) is usually utilized to estimate the graphitization degree. 26,27 However, it could be found that all samples displayed similar I D /I G values, indicating that the carbon components in these composites have a similar graphitization degree. Moreover, TG curves were carried out to determine the weight fractions of f-Fe 2 O 3 in HMCS@f-Fe 2 O 3 -x composites (Figure 3d).…”
Section: Fabrication and Characterization Of Hmcs@f-fe 2 O 3 -X Nanop...mentioning
confidence: 91%
“…[ 200 ] The yolk‐shell structures could also be obtained through coating–coating‐carbonization‐etching process (Figure 15). [ 203 ] The content and concentration of the etching agent determine the size of the yolk core. It is worth noting that the synthesis strategy of CoSnO 3 ‐MOF precursor has been switched from hydrothermal to solvent‐free synthesis, and the obtained CoSn/NC composites maintained the morphologies of nanocubes, which display an RL min of –48.2 dB and an EAB value of 5.84 GHz at 2.2 mm.…”
Section: Microstructure Control Of Mof‐based Mamsmentioning
confidence: 99%